Band formation at interfaces between N-heteropolycycles and gold electrodes - Stein, Arnulf; Rolf, Daniela; Lotze, Christian; Günther, Benjamin; Gade, Lutz H.; Franke, Katharina J.; Tegeder, Petra (The journal of physical chemistry letters, 2021)
Efficient charge injection at organic semiconductor/metal interfaces is crucial for the performance of organic field effect transistors. Interfacial hybrid band formation between electronic states of the organic compound and the metal electrode facilitates effective charge injection. Here, we show that a long-range ordered monolayer of a flat-lying N-heteropolycyclic aromatic compound on Au(111) leads to dispersing occupied and unoccupied interfacial hybrid bands. Using angle-resolved two-photon photoemission we determine their energy level alignment and dispersion relations. We suggest that band formation proceeds via hybridization of a localized occupied molecular state with the d-bands of the Au substrate, where the large effective mass of the d-bands is significantly reduced in the hybrid band. Hybridization of an unoccupied molecular state with the Au sp-band leads to a band with an even smaller effective mass.
Gesehen am 10.09.2021